Individualized optimal release angle in discus throwing - Yu, B.; Leigh, S.; Liu, H. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Release angle is a parameter that significantly influences the official distance through its effects on the vacuum flight distance and the aerodynamic distance (distance gain or lose due to aerodynamic effect) in discus throwing. Significant efforts have been made to determine the optimal release angle for discus throwing. Previous studies on the optimal release angle in discus throwing were based on two critical assumptions: (1) the release angles and the release speeds were independent of each other, and (2) the optimal release angle was the same for all discus throwers. These two assumptions may have been violated in previous studies on the optimal release angle (Hubbard et al., 2001; Linthorne, 2001; Viitasalo et al., 2007). The violation of these two assumptions may have resulted in significant errors in the optimal release angles for discus throwers reported in the current literature. The purposes of this study were: (1) to determine the relationships between the release speed and the release angle for individual discus throwers, (2) to determine the relationships between the aerodynamic distance and the release angle for individual discus throwers, and (3) to determine the optimal release angles for individual discus throwers; using data collected in competition.